Geochemical approach to the genesis of the Oligocene-stratiform manganese-oxide deposit, Chiatura (Georgia) - Sasmaz, Ahmet; Sasmaz, Bilge; Hein, James R. (Elsevier, 2021)
The Chiatura deposit is considered to be among the largest deposits of metallurgical grade manganese ore in the world, yet its geochemistry is poorly known, which is the focus of this paper. The Oligocene sedimentary Mn deposit is located in the Chiatura region of central Georgia and formed in a restricted arm of the Paratethys on stable crystalline basement during a regressive-transgressive cycle. An Oligocene basal conglomerate is overlain by sandstone that is in turn overlain by the ore deposits. The Chiatura sedimentary deposits form horizontal beds, 1.5 to 4 m thick, average 2 m, of which 1 to 1.5 m is high-grade ore, covering an area of some 150 km2. The Chiatura deposit contains three types of ore, primary oxide ores, carbonate ores, and oxidized carbonate ores and this paper focuses on the oxide ores. The common manganese minerals in the oxide ore are manganite, pyrolusite, braunite, and psilomelane, and less commonly bixbyite, rhodochrosite, and vernadite. Eighteen manganese-oxide and four wall-rock (low manganese content) samples were analyzed for geochemistry and found on average 36.6 wt% MnO, 2.45 wt% Fe2O3, 23.5 wt% SiO2, 5.88 wt% Al2O3, 3.84 wt% CaO for major oxide concentrations. The mean main trace element concentrations of the samples are 3944 ppm Ba, 946 ppm Sr, 511 ppm Ni, 150 ppm Zn, 94 ppm V, 84 ppm Cu, and 55 ppm Co. These element concentrations are generally low and indicate an enrichment assemblage of V, Ni, Co, Cu, Zr, As, Ba, Cd, Pb, and Zn. The total rare earth element (REE) concentrations of the deposits vary from 83 ppm to 521 ppm (mean 199 ppm). The Post-Archean Australian Shale (PAAS)-normalized REE concentrations have similar trends and show heavy REE (HREE) enrichments. All manganese-oxide samples show negative Ce (mean 0.58) and generally positive Eu (mean 1.20) anomalies, except for four samples. These geochemical data indicate that the Chiatura deposit precipitated rapidly in oxic seawater with a characteristic negative Ce anomaly. The carbonate and mixed ores compared to the oxide-hydroxide ores formed in a deeper-water environment of the shallow sea. Further, both Pb isotopic data and chemical discrimination diagrams show that the Chiatura deposit was affected by both hydrothermal activity located in deeper water, and by terrestrial input. The manganese metals in the oxide ores were syngenetically transported to the area of mineralization from deeper waters than the region where the carbonate ores formed.
Keywords: Manganese-oxide ore; Oligocene; Stratiform deposit; Trace elements; Rare earth elements; Chiatura; Georgia